A unique case report of mitral valve endocarditis associated with coronary stent infection. Issue 12 (30th November 2021) - Doost, Ata; Rankin, James; Yong, Gerald
Abstract: Background: Despite increasing use of percutaneous coronary intervention and stenting, septic complications such as coronary stent infections are rare. We report a unique case of mitral valve infective endocarditis and associated coronary stent infection which emerged 6 months after index stent insertion. Case summary: A 56-year-old previously healthy man underwent percutaneous coronary intervention and stenting of left circumflex (LCx) coronary artery in the setting of non-ST-segment elevation myocardial infarction. Six months later, he represented with inferior ST-segment elevation myocardial infarction and was found to have a coronary pseudoaneurysm of stented segment of LCx. The pseudoaneurysm was treated with insertion of a covered stent, and immediately following that he developed sepsis with methicillin-sensitive Staphylococcus aureus bacteraemia. Comprehensive work-up resulted in the diagnosis of mitral valve endocarditis complicated by coronary stent infection and myocardial abscess formation. He was managed with initial prolonged systemic antibiotic treatment followed by mitral valve replacement. Post-operative course was uneventful with a short duration of oral antibiotics. At 6-year follow-up, the patient was well with the satisfactory echocardiographic result. Discussion: This is a very rare case of mitral valve endocarditis with extensive cardiac involvement including coronary stent infection and surrounding myocardial abscess. Stents can act as an ideal vector for bacterial adherence from which bacteria could spread to the arterial wall and adjacent myocardium. This case suggests a potential complication of delayed endothelialization and risk of infective complication due to bacterial seeding or embolization.